Monitoring of maize lodging using multi-temporal Sentinel-1 SAR data. Issue 1 (1st January 2020) - Shu, Meiyan; Zhou, Longfei; Gu, Xiaohe; Ma, Yuntao; Sun, Qian; Yang, Guijun; Zhou, Chengquan
Abstract: Lodging is a common phenomenon in maize production, which seriously affects its yield, quality, and mechanical harvesting capacity. With good penetrating power, satellite radar can monitor crop growth even under cloudy weather conditions. In this study, a method based on the change in plant height before and after lodging in maize is proposed to calculate the lodging angle and monitor the lodging degree by using dual-polarization Sentinel-1A data. The results show that the optimal sensitive polarization combinations of maize plant height before and after lodging are VH/VV and VV, respectively. The lodging angle is calculated using the plant height inversion results before and after lodging. The overall accuracy of classifying lodging grade of maize is 67%. The proposed model based on lodging angle could effectively mapped the maize lodging range on a regional scale and classify the lodging grades.